A rare case of lung carcinoma acquires multidrug-resistant Klebsiella pneumoniae pneumonia radiologically mimicking metastasis caused by nivolumab therapy-associated neutropenia - Liu C; Ding L; Zhu Y; Chen C (Dove Medical Press, 2017)
Chao Liu,* Ling Ding,* Ye-han Zhu, Cheng Chen Respiratory Department, The First Affiliated Hospital of Soochow University, Suzhou, People’s Republic of China *These authors contributed equally to this work Abstract: Nosocomial infections by Klebsiella pneumoniae, especially those due to multidrug-resistant strains, are being increasingly detected. In this report, we present the case of a 63-year-old man with lung squamous carcinoma who received nivolumab therapy due to failure of first-line chemotherapy. This report also demonstrates an association of nivolumab therapy and neutropenia, and supports the use of a combination of tigecycline and meropenem in managing hospitalization-acquired pneumonia caused by multidrug-resistant K. pneumoniae. It also implicates that a further evaluation is required in lung cancer patients with a suspected metastatic or recurrent carcinoma, and an antibiotic therapy is valuable in ruling out a potential lung infection since a risk of hospitalization-acquired pneumonia may exist. Keywords: hospitalization-acquired pneumonia, nivolumab, neutropenia, lung carcinoma, multidrug-resistant Klebsiella pneumoniae